Gonadotropin dose selection for repeat IVF cycles in POSEIDON Groups 1 and 2 - Wei, Hao; Duan, JinLiang; Wang, SiShi; Zhu, BaoPing; Jiang, HaiLing (Frontiers in Endocrinology, 2025)
PurposeInvestigating whether increasing the dose of gonadotropins (Gn) in the second in vitro fertilization (IVF) cycle using the antagonist protocol could improve the cumulative live birth rate (CLBR) in POSEIDON Groups 1 and 2.MethodsThis retrospective study included 343 patients from POSEIDON Groups 1 and 2 who underwent two consecutive cycles of ovarian stimulation with an antagonist protocol between May 2018 and September 2022. Patients were divided into an Additive group (those who increased the Gn dosage in the second cycle) and a Control group (those who maintained or decreased the Gn dosage), with a 1:2 propensity score matching analysis. The primary outcome was the CLBR.ResultsIn the second IVF cycle, the Additive group had higher initial (191.8 vs 183.4, P=0.135) and total (2161.7 vs 1770.6, P=0.461) Gn doses compared to the Control group. The Additive group also had a higher average number of retrieved oocytes and Metaphase II (MII) oocytes, a higher two pronuclei (2PN) fertilization rate (3.3 vs 2.6, P=0.065), and higher blastocyst formation rates (44.9% vs 44.2%, P=0.937) compared to the Control group; however, these differences were not statistically significant. The Control group had a slightly higher CLBR (31.5% vs 28.9%, P=0.8), which was also not statistically significant.ConclusionsFor POSEIDON Groups 1 and 2, increasing the dose of Gn under the antagonist protocol increased treatment costs but did not improve the CLBR. Routine increase of Gn dose was not recommended.